Resumos Expandidos : Campus Goiabeiras - Moreira, Éder Carlos; Coelho Fabrino Filho, Leonardo; Moura Gonçalves , Myllena; Araujo de Souza, Henrique; de Almeida Vilela, Daniel; Rodrigues de Souza , Pablo; de Oliveira Salvato , Pablo (Revista Guará, 2023)
-